Clinical predictors of central sleep apnea evoked by positive airway pressure titration - Moro M (Dove Medical Press, 2016)
Marilyn Moro,1 Karen Gannon,1 Kathy Lovell,1 Margaret Merlino,1 James Mojica,2 Matt T Bianchi,1,3 1Neurology Department, 2Pulmonary and Critical Care Medicine, Massachusetts General Hospital, Boston, MA, USA; 3Division of Sleep Medicine, Harvard Medical School, Boston, MA, USA Purpose: Treatment-emergent central sleep apnea (TECSA), also called complex apnea, occurs in 5%–15% of sleep apnea patients during positive airway pressure (PAP) therapy, but the clinical predictors are not well understood. The goal of this study was to explore possible predictors in a clinical sleep laboratory cohort, which may highlight those at risk during clinical management.Methods: We retrospectively analyzed 728 patients who underwent PAP titration (n=422 split night; n=306 two-night). Demographics and self-reported medical comorbidities, medications, and behaviors as well as standard physiological parameters from the polysomnography (PSG) data were analyzed. We used regression analysis to assess predictors of binary presence or absence of central apnea index (CAI) ≥5 during split PSG (SN-PSG) versus full-night PSG (FN-PSG) titrations.Results: CAI ≥5 was present in 24.2% of SN-PSG and 11.4% of FN-PSG patients during titration. Male sex, maximum continuous positive airway pressure, and use of bilevel positive airway pressure were predictors of TECSA, and rapid eye movement dominance was a negative predictor, for both SN-PSG and FN-PSG patients. Self-reported narcotics were a positive predictor of TECSA, and the time spent in stage N2 sleep was a negative predictor only for SN-PSG patients. Self-reported history of stroke and the CAI during the diagnostic recording predicted TECSA only for FN-PSG patients.Conclusion: Clinical predictors of treatment-evoked central apnea spanned demographic, medical history, sleep physiology, and titration factors. Improved predictive models may be increasingly important as diagnostic and therapeutic modalities move away from the laboratory setting, even as PSG remains the gold standard for characterizing primary central apnea and TECSA. Keywords: risk, prediction, central apnea, complex apnea, emergent, titration